Intrusions of textism into students' formal writing: reality or myth? - Saberi, Dariush (Universiti Putra Malaysia Press, 2016)
It is claimed by the media that the expansion of Instant Messaging (IM) in recent years affected the quality of formal writing and there are intrusions into such writings (Grace, Kemp, Martin, & Parrila, 2015). The current study examined six articles published in scientific journals in 2009, 2010, 2012, 2013 and 2015 on textism (e.g. gr8 for “great”) to see if there have been any changes in the results of the studies on the quality of writing under the influence of textism in native and non-native groups during the last 6 years. The population in all three studies has been young adults between 18 to 29 years old, male and female. The studies are done through writing tests in academic institutions and schools. Synchronization of the findings over time is important as it can show that if, with the expansion of social media and increasing number of messaging applications, there has been any significant increase in the textism intrusion or not. The content analysis and statistical comparison are used as the methods to compare the studies’ results and to form an armchair study to validate the effects of the textism on formal writing. Based on the chronological and synthesized results, it was found ultimately that in the native group there is not any significant difference between the results over the synchronized time and the media claims are not true, while the non-native learners of English have shown negative intrusions.